2008
DOI: 10.1161/circulationaha.107.740357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short Call Admission on Length of Stay and Quality of Care for Acute Decompensated Heart Failure

Abstract: Background-In response to residency work hour restrictions, programs restructured call schedules, increasing the use of short call (daytime admitting teams). Few data exist on the effect of short call on quality of patient care. Our objective was to examine the effect of short call admission on length of stay and quality of care for patients with acute decompensated heart failure. Methods and Results-We conducted a retrospective cohort study of 218 patients admitted with acute decompensated heart failure to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Although the literature suggests that patients are subjected to more tests 14 and longer stays due to handoffs in general, 12,13,16,17,20,21 our findings suggest the contrary for end-of-month handoff. In fact, we speculate that when a new team takes over, they emphasize discharge.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Although the literature suggests that patients are subjected to more tests 14 and longer stays due to handoffs in general, 12,13,16,17,20,21 our findings suggest the contrary for end-of-month handoff. In fact, we speculate that when a new team takes over, they emphasize discharge.…”
Section: Discussioncontrasting
confidence: 70%
“…Examples include night-to-day transition (or vice versa), hospitalist shift transition, and weekend coverage transition. Numerous patient safety outcomes have been studied, such as mortality during weekend admission, 11 length of stay related to being admitted to short-call teams, 12 delays in care as a result of inefficient handoff, 13 and more laboratory tests for patients transferred to different residents after admission. 14 Subjectively, among surveyed housestaff, reports of harm to patients from ineffective handoffs were common.…”
mentioning
confidence: 99%
“…The studies by Schuberth et al 7 and Fonarow et al 8 are important steps forward, but they are just the beginning. The organization and financing of healthcare delivery greatly influence the effectiveness of the care received by millions of patients, and yet the volume of high-quality studies that have assessed these issues is far smaller than that of studies that have assessed the efficacy of specific treatments.…”
Section: ;1:50 -57mentioning
confidence: 99%
“…For example, although the study by Fonarow et al 8 had a sample size of 48 612 patients, it was unable to detect a 52% increase in the odds of death comparing weekends with weekdays. The ability to detect clinically significant differences in process of care measures and complications (including death) is even less in the study by Schuberth et al, 7 given the sample size of 218 patients. Both studies also used in-hospital death as an outcome, which is a potential problem because patients who have longer lengths of stay have more opportunities to die in the hospital than do patients who have shorter lengths of stay, 9 although the study by Fonarow et al 8 did examine posthospital discharges in a subset of patients.…”
Section: ;1:50 -57mentioning
confidence: 99%
“…33,34 Increases in the number of handoffs by medical providers to maintain continuity of care has been noted to increase the risk of adverse events. [35][36][37][38] Several studies have also found both equivocal and improved mortality outcomes following implementation of duty hour restrictions. 29,33,34 Due to mixed results, an assessment of morbidity represented by a quality outcome such as HACs, rather than mortality, may be more effective at evaluating patient care and hospital processes following ACGME reform.…”
Section: Bottom Linementioning
confidence: 99%